Kingdomino [games] - Cathala, Bruno (Game designer); Bouquet, Cyril (Blue Orange USA, 2017)
Dominoes with a Kingdom building twist! Each turn, connect a new domino to your existing Kingdom, making sure at least one of its sides connects to a matching terrain Type already in play. The game mechanics for obtaining the tiles is clever: the order of who picks first depends on which tile was previously chosen. Make sure to secure tiles with crowns- these royal treasures help to multiply the worth of your Kingdom at the end of the game! The game ends when each player has completed a 5 x 5 grid, and then points are counted based on number of connecting tiles and crowns.